Latin America in the mirror of their questions - Terán, Óscar (2006)
Almost forty years ago, Martin Stabb published a book about Latin America with a symptomatic title: In Search of an Identity. Today, the question contained in the said acquires validity again for various reasons, although in notoriously diverse circumstances and with intellectual instruments, in part, novel.